2023
DOI: 10.35848/1347-4065/acc872
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological model for predicting C x H y F z + ion etching yields of SiO2 and SiN x substrates

Abstract: In this study, a novel phenomenological model is developed to predict the etching yields of SiO2 and SiNx substrates by fluorocarbon (FC) and hydrofluorocarbon (HFC) ions. The CF layer thickness and reactive layer chemistry are described, which significantly affect the etching yields. The study focuses on the dependence of the atomic component of the ion and the incident ion energy of the ion on the etching yield. Some assumptions enable the calculation of ion etching yields in a short turn-around-time. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…10,[24][25][26][27][28][29][30][31] Kawamoto et al predicted C x H y F z + ion etching yields for SiO 2 and SiN using a phenomenological model. 32) Their work suggested that C x H y F z + ions with x = 2-5 have relatively high etch yields for SiO 2 , and C x H y F z + ions with x = 2-3 would have relatively high etch yields for SiN. Based on this, we assumed that the C x H y F z gases with x = 3-5 would exhibit high plasma dissociation into the previously mentioned fragments.…”
Section: Introductionmentioning
confidence: 94%
“…10,[24][25][26][27][28][29][30][31] Kawamoto et al predicted C x H y F z + ion etching yields for SiO 2 and SiN using a phenomenological model. 32) Their work suggested that C x H y F z + ions with x = 2-5 have relatively high etch yields for SiO 2 , and C x H y F z + ions with x = 2-3 would have relatively high etch yields for SiN. Based on this, we assumed that the C x H y F z gases with x = 3-5 would exhibit high plasma dissociation into the previously mentioned fragments.…”
Section: Introductionmentioning
confidence: 94%